Ontario's Mustard Report: Its Implications For Family Physicians - Mustard, James F. (1974)
In an issue devoted to the theme of Running a Practice: Politics, Philosophy and Economics, it's necessary to look at current developments which may change methods of practice. The following article is drawn from several sources: firstly, there are direct quotations from sections of the Ontario Report of the Health Planning Task Force which deal specifically with primary care; secondly, there are comments from Dr. Fraser Mustard, chairman of the Task Force, made to delegates of the College's Ontario Chapter at a special workshop convened in Toronto to look at the Chapter's role in speaking for that province's family physicians. Finally, College member Dr. Martin Humphrys, himself a member of the Task Force, comments on some of the implications for family practice as he sees them.